Analysis Of Labor Rights After The Job Creation Law In Perspective Of Human Rights - Christina NM Tobing; Sryani Br. Ginting; Hasnul Arifin Melayu (Jurnal Hukum dan Peradilan, 2023)
The Job Creation Law has caused controversy from various circles of society, both in terms of the procedure for its formation and the contents, especially the labor cluster. Many materials in the Job Creation Law reduce workers’ rights by creating a flexible working relationship. The relationship is more in favor of the interests of employers, thus raising the issue of legalizing modern slavery, which is contrary to human rights. This study analyzes changes in workers’ rights, especially regarding wages, specific worktime agreements, outsourcing, and severance pay from a human rights perspective. This research was normative legal research, namely on the substance of workers’ rights after the Job Creation Law from a human rights perspective, with a statutory approach and a conceptual approach. The analysis revealed that the job creation law policy is an effort to create the broadest possible employment opportunities and attract greater investment to Indonesia. In addition, it is to realize the human rights of workers who have not worked. The changes in the Job Creation Law and its implementing regulations that abolish and reduce workers’ rights and make work relations more flexible can violate workers’ human rights. On the other hand, the Government is trying to strike a balance by creating new and fair workers’ rights.